1989
DOI: 10.1051/rnd:19890208
|View full text |Cite
|
Sign up to set email alerts
|

Iodine nutrition in ewes. 2. Effects of low to high iodine intake by ewes on the I content of biological fluids and plasma immunoglobulins G in newborn lambs

Abstract: 2. I intake of ewes had no effect on birthweight, body weight gain, or mortality between birth and wk 2 of life. No difference between the groups was recorded in the weights of brain, heart, lungs, and liver of lambs killed at birth. However, the weight of both the thyroid lobes in lambs from group E was lower than that of the other groups. The I content of the thyroid lobes of lambs from group A was 30-40% lower than that of the other groups.3. The plasma inorganic iodine (PII) of lambs from birth to d42 of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…It has long been recognised that increasing the supply of I to farm livestock increases the circulating concentrations of thyroid hormones (Aumont et al 1989 a , b ). In the pregnant rat, subcutaneous T4 injections immediately prepartum have been shown to reduce the intestinal permeability to macromolecules in the postpartum period (Chan et al 1973).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognised that increasing the supply of I to farm livestock increases the circulating concentrations of thyroid hormones (Aumont et al 1989 a , b ). In the pregnant rat, subcutaneous T4 injections immediately prepartum have been shown to reduce the intestinal permeability to macromolecules in the postpartum period (Chan et al 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The mean concentrations of plasma inorganic iodine in the deficient heifers remained very low (approximately 10 μg/litre) throughout the experimental period, whereas in the sufficient heifers they plateaued at approximately 55 to 60 μg/litre. Aumont and others (1989) recorded plasma inorganic iodine concentrations of approximately 70 μg/litre in pregnant sheep fed a diet with an iodine concentration of 2·01 mg/kg dm . McCoy and others (1995) suggested that the lower normal limit for plasma inorganic iodine concentrations in pregnant cattle was 80 μg/litre.…”
Section: Methodsmentioning
confidence: 99%
“…Except these two studies (Singh et al, 1994;Šlosárková et al, 1999), no other literature about the relation between iodine supplementation and clinical signs of toxoplasmosis was available. We know, that iodine deficiency influences immune system negatively (Jones et al, 1986;Aumont et al, 1989) and that host's immune response has crucial impact on progress of toxoplasmosis (Denkers and Gazzinelli, 1998).…”
mentioning
confidence: 99%